Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

P125 Sex-sorting conventional frozen semen—“reverse sorting”—results in viable pregnancies from ICSI-produced embryos - J.C. Samper; C. Gongora; L. Russel; C.R. Neto; R. Juras; D. Scofield (Journal of Equine Veterinary Science, 2026)

Comparative Effects of Thermal Recovery Strategies on Strength, Muscle Soreness and Molecular Markers Following Exercise-Induced Muscle Damage in Healthy Adults - F. Bayne; M. Nagyova; N. Stolk; M.A. Placido; M. Hamdi; A. Falzon; R. Perezen; S. Neto Menezes; S. Haliti; C. Atkinson; S. Racinais; N. Gaoua (Journal of Thermal Biology, 2026)

Petasma as a Reliable External Indicator of Male Sexual Maturity in Penaeus schmitti : Integrating Morphological, Biometric and Histological Analyses - H. Castro‐Neto; C. Craveiro; M. G. do Rêgo; P. G. V. Oliveira; R. Soares; S. Peixoto (Fisheries Management and Ecology, 2026)
Understanding male sexual maturity in penaeid shrimp is crucial for stock assessment and size‐based management; however, maturity criteria remain heavily biased toward females and rarely validated for males. This study evaluated whether petasma fusion is a reliable external indicator of male sexual maturity in white shrimp Penaeus schmitti from Northeast Brazil and estimated size at first maturation using an integrative morphometric, histological, and statistical approach. Forty‐five males were classified according to petasma condition, morphometrically measured, histologically examined along the reproductive tract, and analyzed using individual‐level binomial logistic regression. The estimated cephalothorax length at first maturation was CL 50 = 2.24 cm (95% CI: 2.06–2.43), with a strong model performance (Nagelkerke R 2 = 0.80). Histological analysis revealed complete categorical agreement between external morphology and internal reproductive status: all males with unfused petasma lacked mature spermatozoa and exhibited only early germ cells, whereas all males with fused petasma presented the complete spermatogenic series and fully differentiated spermatozoa in the terminal ampulla. The relationship between petasma length and body size showed negative allometry, indicating a proportionally smaller investment in petasma growth relative to somatic growth. ANCOVA detected a significant maturity effect on the intercept, but not on the slope, demonstrating a discrete proportional change in petasma dimensions at maturation, rather than a change in growth trajectory. These findings demonstrate that petasma fusion is a robust and nondestructive indicator of physiological maturity in male P. schmitti . The results of the analysis combining petasma, histology, and length at first maturity indicated that petasma is a reliable indicator for validating physiological maturity and that male reproductive indicators should be formally incorporated into penaeid fishery management structures.

Olfactory bulb 6-OHDA neurotoxicity as a model of early cortical dysfunction - Edson Fiorenza-Neto; Bruna B. Gattiboni; Karin Almeida; Luis F. Marqueze; Bassam F. Mogharbel; Juliana R. N. de Aguiar; Larissa C. Marques; Larissa R. Lazarini; Stephanie R. S. Carvalhal; Angelica Boldt; Ricardo C. Cunha; Katherine A. T. Carvalho; et al. (Molecular and Cellular Biochemistry, 2026)
The olfactory bulb (OB) is one of the earliest brain regions affected in neurodegenerative diseases such as Parkinson’s disease (PD). Its high metabolic rate, dopaminergic modulation, and connectivity with the cortical and limbic regions make it particularly vulnerable to early neuroinflammatory and oxidative processes. This study aimed to investigate whether the administration of 6-hydroxydopamine (6-OHDA) into the OB induces behavioral, redox, and inflammatory alterations associated with early cortical disturbances. Male Wistar rats were randomly assigned to the sham or 6-OHDA groups and underwent stereotaxic injection of the vehicle or 6-OHDA into the left OB. Behavioral performance was assessed in the open-field test 12 days after surgery, and cortical tissue was collected for biochemical and molecular analyses. Cytokines (IL-1β, IL-6, TNF-α, IL-10, IFN-γ, and MCP-1) were quantified by Luminex, redox parameters (CAT, GPx, MDA, and protein carbonyls) by spectrophotometry, and neuronal signaling proteins (c-FOS, CREB, and BDNF) by qPCR. Animals with 6-OHDA lesions exhibited decreased latency and increased time spent in the central zone of the open field, indicating altered exploratory behavior. IL-6 levels were significantly elevated, whereas IFN-γ was reduced in the cortex, while IL-1β, TNF-α, MCP-1, and IL-10 remained unchanged. The oxidative stress markers MDA and protein carbonyls were increased, while catalase and glutathione peroxidase activities showed no change. The expression of c-FOS, CREB, and BDNF was not significantly modified. These findings indicate that localized 6-OHDA administration in the OB is sufficient to elicit behavioral, inflammatory, and oxidative alterations in connected cortical regions, which may resemble early non-motor features associated with olfactory dysfunction, without representing a neurodegenerative disease-specific process.

Toward energy self-sufficiency in small municipal wastewater treatment plants: assessment of energy recovery potential, process economic balance, and greenhouse gas avoidance - Fernanda Amaral-Góis; Vinicius J. Silva; Renan C. Testolin; Ramaiana Radetski-Silva; Dilamara R. Scharf; Marcelo Poyer-Radetski; Wendell Pimentel-Almeida; Cleder A. Somensi; Rafael Ariente-Neto; Claudemir M. Radetski (Environmental Science and Pollution Research, 2026)
The objective of this study was to quantitatively assess the energy recovery potential from both biogas and the incineration of dewatered sludge, aiming to meet the energy demand of a small municipal wastewater treatment plant (MWTP) with a treatment capacity below 50 L s −1 . The energy potential of sludge incineration was characterized based on its gross calorific value, while energy production from biogas generated during the anaerobic digestion of municipal sludge was also evaluated. In addition, the feasibility of using the produced biogas for the thermal drying of dewatered sludge was analyzed. The results indicate that biogas utilization could generate 1462 kWh d −1 , corresponding to 83.17% of the total electricity consumption of the MWTP. Furthermore, the mass reduction achieved through sludge drying resulted in an annual cost savings of US$ 27,763 related to sludge disposal. The incineration of dried sludge could generate an additional 432.52 kWh d −1 . Overall, the combined energy recovery strategy could lead to a reduction of approximately 150 t CO 2 eq year −1 in greenhouse gas emissions due to methane avoidance at the studied MWTP. These findings suggest that such integrated approaches can encourage investments in MWTPs aimed at achieving energy self-sufficiency while enhancing environmental performance. Graphical abstract

Repellent activity and toxicity of the essential oil of Calyptranthes concinna DC. using the model insect Drosophila melanogaster - M. S. Costa; T. S. Freitas; M. A. S. Oliveira; N. J. S. Araujo; S. P. Silva; Z. S. Silveira; N. S. Macêdo; J. C. Andrade-Pinheiro; H. S. Santos; A. M. R. Teixeira; F. A. B. Cunha; Ivo C. Pita Neto; et al. (Brazilian Journal of Botany, 2026)
Insects, belonging to the phylum Arthropoda, play essential roles in ecosystems, play essential roles in ecosystems, such as pollination, pest control, and decomposition. However, some species are vectors of diseases, which makes the development of control methods crucial. The use of synthetic insecticides, although effective, causes serious environmental and health problems. As an alternative, plant essential oils, which are biodegradable and can have repellent and toxic effects on insects, have gained prominence. This study focuses on the species Calyptranthes concinna DC., belonging to the Myrtaceae family, whose repellent and toxicological properties were evaluated using Drosophila melanogaster Meigan (1830) as an experimental model. The botanical material of Calyptranthes concinna was collected from the Private Natural Heritage Reserve in Palmeira-PR, and the essential oil was extracted from the dried leaves by hydrodistillation. The oil, with a yield of 0.26%, was stored for later analysis. The species Drosophila melanogaster was used as a model for toxicity and repellent activity tests. The tests involved fumigation of flies with different doses of oil, evaluation of damage to locomotor capacity and repellency test using filter paper. Data were analyzed statistically using two-way ANOVA. Calyptranthes concinna essential oil demonstrated low toxicity to Drosophila melanogaster , with 100% survival at all concentrations tested over 48 h and deaths that were not statistically significant compared to the water control. Impairment of locomotor capacity was observed only at the highest concentrations (40 µg/mL) after 3 h, and at intermediate concentrations (20 µg/mL) after 6 h, but these effects were equal to the control after 12 h. The repellency test revealed that the essential oil has a significant efficacy, especially at higher concentrations (39 µg/cm 2 ), comparable to the commercial repellent DEET, indicating that C. concinna essential oil is a promising alternative to synthetic repellents. Calyptranthes concinna essential oil has demonstrated potential as a natural repellent, with low toxicity and efficacy comparable to commercial DEET. Compared to studies with other essential oils and similar compounds, C. concinna oil has shown consistent results, suggesting that it may be an effective and environmentally friendly alternative to synthetic repellents. The presence of terpenes in the essential oil may be related to its repellent effect. These results support the use of C. concinna essential oil as a promising natural repellent.

Parkia platycephala pod meal as a total replacement for Tifton-85 hay in high-concentrate diets for lambs: ingestive behavior, physiological, and metabolic parameters - Henrique N. Parente; Vanilsa C. Sousa; Gabrielle M. Oliveira; Osmar M. F. Neto; Gisele T. A. Silveira; Aylpy R. D. Santos; Juliana D. Oliveira; Anderson M. Zanine; Daniele J. Ferreira; Miguel A. Moreira Filho; Michelle O. M. Parente (Tropical Animal Health and Production, 2026)

Implementation of electrochemical treatment unit in an integrated offshore produced water treatment system - E. E. Schneider; M. A. P. Cechinel; S. E. Weschenfelder; D. G. Della Rocca; M. L. A. Albuquerque; S. L. de Carvalho Neto; L. P. Mazur; C. J. de Andrade; D. de Oliveira; R. F. P. M. Moreira (International Journal of Environmental Science and Technology, 2026)

First experimental determination of the 40Ar(n,2n)39Ar reaction cross section and 39Ar production in Earth’s atmosphere - S. Bhattacharya; M. Paul; R.N. Sahoo; R. Purtschert; H.F.R. Hoffmann; M. Pichotta; K. Zuber; D. Bemmerer; T. Döring; R. Schwengner; M.L. Avila; E. Lopez-Saavedra; et al. (Geochimica et Cosmochimica Acta, 2026)

Longitudinal effects of cerebrovascular reactivity and cerebral pulsatility in cognitively intact older adults with APOE4: links with cognition - Zacharie Potvin-Jutras; Pierre-Luc Tremblay; Hanieh Mohammadi; Sylvia Villeneuve; R. Nathan Spreng; Claudine J. Gauthier; Sylvia Villeneuve; Judes Poirier; John C.S. Breitner; Jennifer Tremblay-Mercier; Jordana Remz; Jean-Michel Raoult; et al. (GeroScience, 2025)

Combined use of electrochemical, dissolved air flotation, and microfiltration in the treatment of offshore produced water - M. A. P. Cechinel; M. C. Proner; D. G. Della Rocca; S. L. de Carvalho Neto; S. E. Weschenfelder; A. da Silva; A. Ambrosi; M. Di Luccio; R. F. P. M. Moreira (International Journal of Environmental Science and Technology, 2025)

Genetic correlations between carcass traits measured by ultrasonography and semen quality traits in Nellore cattle incorporating genomic information - Camila S. Mussi; Gabriel C. Medeiros; Rafael Espigolan; Fernando Baldi; Marcio R. Silva; José D. Guimarães; Elisangela C. Matos; Joanir P. Eler; Tamires Miranda Neto; José Bento S. Ferraz; Luiz F. Brito (Livestock Science, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

An outbreak of Urochloa decumbens intoxication in goats from Northeast Brazil - Silvio M.C. Fonseca; Givaldo B. Silva Filho; Elizandra T. Melo; Andrezza C. Andrade; José R.P. Santos; Maria Luiza S.L. Frota; Joaquim Evêncio-Neto; Telma S. Lima; Paula R. Pereira; David Driemeier; Fábio de Souza Mendonça (Toxicon, 2025)

Management of retained fetal membranes by umbilical vessel infusion in mares submitted to elective C-section - Marcos Eduardo Neto; Bruna R. Curcio; Leandro A. Rafael; Giovana M. Pivato; Gabriela C. Silva; Rafaela P. Souza; Mariana A. Mousquer; Carlos E.W. Nogueira (Journal of Equine Veterinary Science, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Assessing muskrat predation on a freshwater mussel assemblage in a southeastern United States river - Brileigh V. Hicks; Augustin C. Engman; Jeronimo G. Da Silva Neto; Caitlin S. Carey; Julianna J. Jett; Gerald R. Dinkins (Food Webs, 2025)

Insecticidal efficacy and chemical profile of Handroanthus impetiginosus extracts for sustainable management of the coffee leaf miner (Leucoptera coffeella) - Andriely B. Silva; Daniel L. Montagnini; Albert Katchborian-Neto; Miller Santos Ferreira; João V. Andrade; Guilherme Otoni Francisco; Pedro S. S. R. Cavallari; Samarah G. Almeida; Enes P. Barbosa; Wilson R. Cunha; Marisi G. Soares; Murilo de Oliveira Souza; et al. (Journal of Plant Diseases and Protection, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Industry 4.0 technologies moderately spurred micro-level circular economy considering cleaner production, not promoting sustainable performance - G. C. de Oliveira Neto; D. da Silva; V. D. Arns; H. N. P. Tucci; L. F. R. Pinto; M. N. Seri (International Journal of Environmental Science and Technology, 2025)

Abundance of two Guiana dolphin ( Sotalia guianensis ) populations inhabiting adjacent areas in southeastern Brazil - Rafael R. Carvalho; Carlos Eduardo P. Quintana; Carlos Vinícius C. dos Santos; Elitieri B. Santos‐Neto; Lis Bittencourt; Karina S. Pereira; Tatiana L. Bisi; Maja Kajin; José Lailson‐Brito; Alexandre F. Azevedo (Marine Mammal Science, 2025)
Guiana dolphins ( Sotalia guianensis ) are commonly found in shallow waters from South and Central America. From March 2018 to June 2019, boat surveys were conducted to monitor two populations inhabiting the adjacent waters of Ilha Grande Bay and Sepetiba Bay to estimate population abundances and population parameters of apparent survival and capture probability. Photo‐identification was used as a mark‐recapture technique. A total of 672 dolphins was cataloged in Ilha Grande Bay and 826 in Sepetiba Bay, with two individuals being photographed in both areas. Population parameters were estimated through mark‐recapture models and total population abundance was estimated at 1,949 and 1,560 individuals in Ilha Grande Bay and Sepetiba Bay, respectively. Seasonal estimates were modeled showing that the Sepetiba Bay population may have stronger site fidelity to the study area than individuals in Ilha Grande Bay. Apparent survival was estimated in a mixed model framework avoiding bias due to the large presence of transient individuals. The estimates presented here are a result of an effort conducted months after an unusual mortality event linked to Guiana dolphin cetacean morbillivirus and our findings indicated that surviving individuals did not have long‐term deadly effects, but continuous efforts should be considered for a long‐term evaluation.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Combined exercise-induced modulation of Notch pathway and muscle quality in senescence-accelerated mice - Ana P. Pinto; Ângelo Augusto J. Sarni; Maria Eduarda A. Tavares; Alisson L. da Rocha; Ruither O. Gomes Carolino; Ivo V. de Sousa Neto; Driele C. Da Silva Ferreira; Vitor R. Munoz; Giovana R. Teixeira; Fernando M. Simabuco; José R. Pauli; Dennys E. Cintra; et al. (Pflügers Archiv - European Journal of Physiology, 2025)

Genetic diversity, drug resistance, and biofilm formation in Klebsiella pneumoniae associated with nosocomial infection in Pelotas, RS, Brazil - Daniela R. Wozeak; Isabel L. Pereira; Thayná L. Cardoso; Amilton C. P. S. Neto; Daiane D. Hartwig (Brazilian Journal of Microbiology, 2025)

Improving survival and growth of caprine preantral follicles cultured in medium commonly used for MSC: Role of oxidative stress regulation and epigenetic changes - Ana F.B. Silva; Laritza F. Lima; Anna C.A. Ferreira; Ariclécio C. Oliveira; Napoleão M.A. Neto; Benner G. Alves; Ana P.R. Rodrigues; Eduardo L. Gastal; Vilceu Bordignon; José R. Figueiredo (Domestic Animal Endocrinology, 2025)

Unveiling unexpected Coffea arabica genetic diversity in Southeast Asia: Timor-Leste and the Philippines - C. Montagnon; M. Baltazar; M. Nogueira; J. dos Santos; E. Umaña; J. C. Berny Mier y Teran; H. Trindade; G. Vieira Martins; N. Neto; R. Mau (Genetic Resources and Crop Evolution, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Microarray data analysis of antileukemic action of Cinnamoylated benzaldehyde LQB-461 in Jurkat cell line - Rachell R. C. Thimoteo; Pedro Nicolau Neto; Debora S. S. Costa; Fabrício da Mota Ramalho Costa; Douglas Cazaroti Brito; Paulo R. R. Costa; Tatiana de Almeida Simão; Ayres G. Dias; Graça Justo (Molecular Biology Reports, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Drowned barriers and valleys: A morphological archive of base level changes in the western South Atlantic - Antonio R. Ximenes Neto; Valéria S. Quaresma; Pedro S. Menandro; Paulo H. Cetto; Alex C. Bastos (Marine Geology, 2024)

Insecticidal activity of extracts of handroanthus impetiginosus on Plutella xylostella (Lepidoptera: plutellidae) larvae - Andriely B. Silva; Daniel L. Montagnini; Albert Katchborian-Neto; João V. Andrade; Hallana A. Manuquian; Pedro S. S. R. Cavallari; Samarah G. Almeida; Enes P. Barbosa; Wilson R. Cunha; Marisi G. Soares; Mario F. C. Santos; Márcio L. A. Silva; et al. (Natural Product Research, 2024)

Trade and socioeconomic importance of an invasive giant snail in the endemic‐rich island of São Tomé, Central Africa - Martina Panisi; Ana R. Pereira; Bruzinay C. Neto; Paulo J. de Sousa; Gabriel Oquiongo; Jorge M. Palmeirim; Ricardo F. de Lima; Ana Nuno (Conservation Biology, 2024)
Managing invasive species is crucial to mitigate their negative impacts on ecosystems, yet conflicts may arise when their social benefits are disregarded. Human pressure on the endemic‐rich forests of São Tomé has been high since the island was discovered by the Portuguese in the 15th century, and numerous species have been introduced. These include the invasive West African giant land snail ( Archachatina marginata ), which was introduced in the mid‐20th century, is now widespread on the island, and is a potential threat to native flora and fauna. We assessed the frequency of consumption of this species and its socioeconomic importance to people across the island with household questionnaires, focus group discussions, and semistructured interviews. We explored the prevalence and potential drivers of use (e.g., wealth, household composition, and diversity of occupations) and characterized the commodity chain to identify demographic groups linked to the snail trade. We interviewed 672 people (1 person per household), conducted 6 focus groups, and interviewed 80 key actors belonging to 5 subcategories. The snail was the most widely consumed bushmeat and an important source of income, particularly for women and unemployed youth. Insecure and scarce livelihood alternatives, mostly in rural areas, were reported as drivers for trade involvement. Snail harvesting was more frequent in poorer households with low occupational diversity. Selling tended to occur in households that were well‐established in the community and had a higher proportion of children. Both were stimulated by the proximity of communities to the native forest. Buying snails was common in all demographic groups, but it was linked to wealth and occupational diversity. Interventions to manage the impact of this introduced species on the valuable ecosystems of the island should involve multiple sectors of society to ensure societal support. This requires robust consideration of the welfare of vulnerable demographic groups that benefit from the species.

Reply to comment on “The passive margin of the southern São Francisco paleocontinent, metamorphic record and implications for the assembly of West Gondwana: Evidence from the Lima Duarte Nappe, Ribeira orogen (SE Brazil)” by Trouw and Ribeiro - Brenda C. Rocha; Mario C. Campos Neto; Caue R. Cioffi; Alice Westin; Adriana Alves; Claudio A. Salazar-Mora; Marcos Egydio-Silva; Renato Moraes; Sara dos S. Souza; Victor C. Maurer (Precambrian Research, 2024)

Investigation of Rabies virus in wild mammals of the atlantic forest in Rio de Janeiro, Brazil - M. Cocchi; C. M. Barboza; J. G. Garcia; R. M. Zamudio; A. Champi; R. L. M. Novaes; S. F. Costa-Neto; R. Moratelli; H. B. C. R. Batista (Brazilian Journal of Microbiology, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Bioadhesive Polymeric Films Containing Rhamnolipids, An Innovative Antimicrobial Topical Formulation - Jéssica B. Carra; Kamila B. B. Wessel; Giovana N. Pereira; Mariana C. Oliveira; Pietra M. T. Pattini; Bianca L. Masquetti; Ismael R. Amador; Marcos L. Bruschi; Rúbia Casagrande; Sandra R. Georgetti; Waldiceu A. Verri; Gerson Nakazato; et al. (AAPS PharmSciTech, 2024)

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Pan-African granitic magmatism of the Kaoko Belt: Tectonic perspective from its South American connection and insights into the crustal architecture of SW Gondwana - Mathias Hueck; Miguel A.S. Basei; Hartwig Frimmel; Lucas M. Lino; Vinicius X. Corrêa; Lucas R. Tesser; Mario C. Campos Neto; Carlos E. Ganade (Precambrian Research, 2024)

The passive margin of the southern São Francisco paleocontinent, metamorphic record and implications for the assembly of West Gondwana: Evidence from the Lima Duarte Nappe, Ribeira Orogen (SE Brazil) - Brenda C. Rocha; Mario C. Campos Neto; Caue R. Cioffi; Alice Westin; Adriana Alves; Claudio A. Salazar-Mora; Marcos Egydio-Silva; Renato Moraes; Sara dos S. Souza; Victor C. Maurer (Precambrian Research, 2024)

Telocytes: current methods of research, challenges and future perspectives - Bruno D. A. Sanches; Francisco B. S. Teófilo; Mathieu Y. Brunet; Victor M. Villapun; Kenny Man; Lara C. Rocha; Jurandyr Pimentel Neto; Marta R. Matsumoto; Juliana S. Maldarine; Adriano P. Ciena; Sophie C. Cox; Hernandes F. Carvalho (Cell and Tissue Research, 2024)

Is a recent large expansion of a no-take reserve sufficient to change the reef fish assemblage? A before-after assessment in Alcatrazes Wildlife Refuge, Southwestern Atlantic - Fernanda A. Rolim; Fernando Z. Gibran; Leonardo M. Neves; Natalia C. Roos; Guilherme H. Pereira-Filho; Gabriel R. Souza; Domingos Garrone-Neto; Fabio S. Motta (Ocean & Coastal Management, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

Melatonin acts through different mechanisms to control oxidative stress and primordial follicle activation and survival during in vitro culture of bovine ovarian tissue - Bianca R. Silva; Francisco C. Costa; Miguel F. De Lima Neto; Francisco F. Caetano Filho; Ernando I.T. de Assis; Francisco L.N. Aguiar; Anderson W.B. Silva; Solano D. Martins; Valdevane R. Araújo; Maria H.T. Matos; José J.N. Costa; José R.V. Silva (Domestic Animal Endocrinology, 2024)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Preliminary assessment of toxicity of aerosol samples from central-west Brazil using Artemia spp. bioassays - Habdias A. Silva-Neto; Valtencir Zucolotto; Emmanuel B. D'Alessandro; Maria G.O. Tavares; Nelson R. Antoniosi Filho; Wendell K.T. Coltro; Guilherme M. Grosseli; Pedro S. Fadini; Roberta C. Urban (Chemosphere, 2023)

Optimisation of LDI(+)-FT-ICR MS analysis of asphaltenes to prevent the formation of fullerenes - Victor R. Fonseca; Gabriely S. Folli; Lindamara M. Souza; Thieres M.C. Pereira; Guilherme S.V. Lima; Carla C.B. Viegas; Luiz S. Chinelatto; Álvaro C. Neto; Paulo R. Filgueiras; Valdemar Lacerda; Wanderson Romão (Fuel, 2023)

In vivo evaluation of analgesic and anti-inflammatory activity of hydroalcoholic extracts from Handroanthus impetiginosus and their chemical composition by UPLC/MS analysis - Ìcaro E. F. Da Silva; Daniela G. Zoca; Gabriela N. Andrade e Silva; Albert Katchborian-Neto; Pedro S. dos S. R. Cavallari; Samarah G. de Almeida; Ana H. Januário; Patricia M. Pauletti; João Victor Andrade; Raquel P. Morais-Urano; Wilson Roberto Cunha; Mario F. C. Santos; et al. (Natural Product Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

New bicyclic [3.2.1] octane neolignan derivative from Aniba firmula - Mario F. C. Santos; Cristiane dos R. Feliciano; Albert K. Neto; Daniela A. Chagas de Paula; Marisi G. Soares (Natural Product Research, 2023)

Mechanical behavior of cementitious composites reinforced with the fiber of sugarcane bagasse and glass wool waste - J. Preve Machado; T. C. da Silva; C. Henrique Borgert; L. Rosso Neto; D. Batista Gesuino; J. R. de Oliveira; T. Elias Allievi Frizon; F. Fardin Grillo; E. Junca (International Journal of Environmental Science and Technology, 2023)

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Characterization of Multidrug-Resistant Staphylococcus aureus Isolates and Comparison of Methods of Susceptibility to Vancomycin - Danillo S. Rosa; Samily A. S. Oliveira; Renata F. S. Souza; Amaro A. S. Neto; Letícia S. B. Cunha; Antônio W. C. Fernandes; Ianka F. S. Soares; Sarah K. R. Teixeira; Samuel R. Aquino; Gisele V. Gouveia; Jackson R. G. S. Almeida; Carine R. Naue; et al. (Current Microbiology, 2022)

Normal echocardiographic and radiographic reference values for crab-eating fox (Cerdocyon thous) anesthetized with ketamine and midazolam - Victor R. F. Ribeiro; Ariana F. Ramos; Angélica Alfonso; Alicia G. Hippolito; Heloísa C. Lima; Viviane M. Codognoto; Diogo C. S. Silva; Miriam H. Tsunemi; Moacir L. Neto; Alessandra Melchert; Priscylla T. C. G. Okamoto; Luiz H. A. Machado; et al. (Veterinary Research Communications, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Genetic structure and management of the Neotropical migratory fish Megaleporinus obtusidens on a highly impacted river basin - Karine K. C. Oliveira-Farias; Renata S. Farias; Miguel A. S. Neto; Marília E. de Souza; Leonardo L. Calado; Martin A. Montes; Ana P. S. Lima; Paulino Martinez; Maria R. M. Coimbra (Hydrobiologia, 2022)

An updated review on bacterial community composition of traditional fermented milk products: what next-generation sequencing has revealed so far? - Gilberto V. de Melo Pereira; Dão Pedro de Carvalho Neto; Bruna L. Maske; Juliano De Dea Lindner; Alexander S. Vale; Gabriel R. Favero; Jéssica Viesser; Júlio C. de Carvalho; Aristóteles Góes-Neto; Carlos R. Soccol (Critical Reviews in Food Science and Nutrition, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Treatment of gaseous effluent using a microalgae-based system - T. A. Pagioro; A. O. Rico; M. Soares; A. C. Sakuma; A. F. dos Anjos; P. R. da Costa Neto; M. Tiboni; J. D. Fontana (International Journal of Energy and Water Resources, 2021)

Acute toxicity, antinociceptive, and anti-inflammatory activities of the orally administered crotamine in mice - Lorena A. Moreira; Lanussy P. Oliveira; Marta R. Magalhães; Sayonara A. M. Oliveira; Jerônimo R. Oliveira-Neto; Pablinny M. G. Carvalho; Adryano A. V. Carvalho; James O. Fajemiroye; Alessandro C. Cruz; Luiz C. Cunha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Effect of a reservoir network on drought propagation in a semi-arid catchment in Brazil - Simone C. H. van Langen; Alexandre C. Costa; Germano G. Ribeiro Neto; Pieter R. van Oel (Hydrological Sciences Journal, 2021)

Storage of Brazilian Cattleya seeds from diverse biomes: lipid composition and effects on germination - Mariane M. Hengling; Thiago M. R. Gianeti; Silvério T. Hosomi; Nelson B. Machado-Neto; Ceci C. Custódio (Plant Biosystems, 2021)

Detection and application of novel SSR markers from transcriptome data for Astronium fraxinifolium Schott, a threatened Brazilian tree species - Maiara R. Cornacini; Ricardo O. Manoel; Marcelo A. M. Alcantara; Mário L. T. Moraes; Edvaldo A. A. Silva; Leonel G. Pereira Neto; Alexandre M. Sebbenn; Bruno C. Rossini; Celso L. Marino (Molecular Biology Reports, 2021)

Petroleum-contaminated soil: using sonolysis to improve mineralization and biodegradation potential of Fenton reaction and ozonolysis process - Renan C. Testolin; Luciana Mater; Ramaiana Radetski-Silva; Eric Sanches-Simões; Wendell Pimentel-Almeida; Gabriela T. Schmidt; Rafael Ariente-Neto; Albertina X. R. Corrêa; Cleder A. Somensi; Claudemir M. Radetski (Environmental Science and Pollution Research, 2021)

Salt tolerance of Calotropis procera begins with immediate regulation of aquaporin activity in the root system - Maria R. V. Coêlho; Rebeca Rivas; José R. C. Ferreira-Neto; João P. Bezerra-Neto; Valesca Pandolfi; Ana Maria Benko-Iseppon; Mauro G. Santos (Physiology and Molecular Biology of Plants, 2021)

Potentiation of Antibiotic Activity by a Meldrum’s Acid Arylamino Methylene Derivative against Multidrug-Resistant Bacterial Strains - Maria M. C. da Silva; José B. de Araújo-Neto; Ana C. J. de Araújo; Priscilla R. Freitas; Cícera D. de M. Oliveira-Tintino; Iêda M. Begnini; Ricardo A. Rebelo; Luiz E. da Silva; Sandro L. Mireski; Michele C. Nasato; Maria I. L. Krautler; Jaime Ribeiro-Filho; et al. (Indian Journal of Microbiology, 2021)

Tropical peatlands and their contribution to the global carbon cycle and climate change - Kelly Ribeiro; Felipe S. Pacheco; José W. Ferreira; Eráclito R. de Sousa‐Neto; Adam Hastie; Guenther C. Krieger Filho; Plínio C. Alvalá; Maria C. Forti; Jean P. Ometto (Global Change Biology, 2021)
Peatlands are carbon‐rich ecosystems that cover 185–423 million hectares (Mha) of the earth's surface. The majority of the world's peatlands are in temperate and boreal zones, whereas tropical ones cover only a total area of 90–170 Mha. However, there are still considerable uncertainties in C stock estimates as well as a lack of information about depth, bulk density and carbon accumulation rates. The incomplete data are notable especially in tropical peatlands located in South America, which are estimated to have the largest area of peatlands in the tropical zone. This paper displays the current state of knowledge surrounding tropical peatlands and their biophysical characteristics, distribution and carbon stock, role in the global climate, the impacts of direct human disturbances on carbon accumulation rates and greenhouse gas (GHG) emissions. Based on the new peat extension and depth data, we estimate that tropical peatlands store 152–288 Gt C, or about half of the global peatland emitted carbon. We discuss the knowledge gaps in research on distribution, depth, C stock and fluxes in these ecosystems which play an important role in the global carbon cycle and risk releasing large quantities of GHGs into the atmosphere (CO 2 and CH 4 ) when subjected to anthropogenic interferences (e.g., drainage and deforestation). Recent studies show that although climate change has an impact on the carbon fluxes of these ecosystems, the direct anthropogenic disturbance may play a greater role. The future of these systems as carbon sinks will depend on advancing current scientific knowledge and incorporating local understanding to support policies geared toward managing and conserving peatlands in vulnerable regions, such as the Amazon where recent records show increased forest fires and deforestation.

Correction to: α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Assessing drought in the drylands of northeast Brazil under regional warming exceeding 4 °C - Jose A. Marengo; Ana Paula M. A. Cunha; Carlos A. Nobre; Germano G. Ribeiro Neto; Antonio R. Magalhaes; Roger R. Torres; Gilvan Sampaio; Felipe Alexandre; Lincoln M. Alves; Luz A. Cuartas; Karinne R. L. Deusdará; Regina C. S. Álvala (Natural Hazards, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Relationship between gain rate during the growing phase and forage allowance in the finishing phase in Nellore cattle - Verônica A. C. Mota; Rodolfo M. Fernandes; Laura F. Prados; João A. Alves Neto; Guilherme F. Berti; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2020)

Helminth metacommunity of small mammals in a Brazilian reserve: the contribution of environmental variables, host attributes and spatial variables in parasite species abundance - T. S. Cardoso; S. F. Costa-Neto; C. Braga; M. Weksler; R. O. Simões; A. Maldonado; J. L. Luque; R. Gentile (Community Ecology, 2020)
The role of environmental factors and landscape heterogeneity on species distribution on different spatial scales is one of the most important questions in community ecology. Variations in the environmental gradient characteristics, host attributes and spatial scales may influence the parasites distribution. The helminth metacommunity of 12 small mammal species was investigated in an Atlantic Forest reserve located in the State of Rio de Janeiro, southeast Brazil. We evaluated the influence of environmental variables, host attributes and spatial factors on the helminth metacommunity of small mammals, considering infracommunity and component community levels. Twenty-nine helminth morphospecies were recovered. The host attributes and spatial variables influenced the abundance of helminth species in the metacommunities for rodents and marsupials together, and for rodents alone at the infracommunity level. Host body mass, host diet and spatial variables at broad spatial scale (among localities) were the most important variables to explain the variation in helminth abundance. Parasite species richness influenced this variation only for the marsupial helminth metacommunity at the infracommunity level. The metacommunity showed larger turnover (parasite replacement) than nestedness (parasite loss) for their helminth species at both infracommunity and component community levels, which is associated with a high host specificity, and low helminth sharing among hosts for most species, resulting in a structured metacommunity.

Concise review of the species Pterocladiella capillacea (S.G. Gmelin) Santelices & Hommersand - R. F. Patarra; C. Iha; L. Pereira; A. I. Neto (Journal of Applied Phycology, 2020)

Urban wild meat consumption and trade in central Amazonia - Hani R. El Bizri; Thaís Q. Morcatty; João Valsecchi; Pedro Mayor; Jéssica E. S. Ribeiro; Carlos F. A. Vasconcelos Neto; Jéssica S. Oliveira; Keilla M. Furtado; Urânia C. Ferreira; Carlos F. S. Miranda; Ciclene H. Silva; Valdinei L. Lopes; et al. (Conservation Biology, 2020)
The switch from hunting wild meat for home consumption to supplying more lucrative city markets in Amazonia can adversely affect some game species. Despite this, information on the amounts of wild meat eaten in Amazonian cities is still limited. We estimated wild meat consumption rates in 5 cities in the State of Amazonas in Brazil through 1046 door‐to‐door household interviews conducted from 2004 to 2012. With these data, we modeled the relationship between wild meat use and a selection of socioeconomic indices. We then scaled up our model to determine the amounts of wild meat likely to be consumed annually in the 62 urban centers in central Amazonia. A total of 80.3% of all interviewees reported consuming wild meat during an average of 29.3 (CI 11.6) days per year. Most wild meat was reported as bought in local markets (80.1%) or hunted by a family member (14.9%). Twenty‐one taxa were cited as consumed, mostly mammals (71.6%), followed by reptiles (23.2%) and then birds (5.2%). The declared frequency of wild meat consumption was positively correlated with the proportion of rural population as well as with the per capita gross domestic product of the municipality (administrative divisions) where the cities were seated. We estimated that as much as 10,691 t of wild meat might be consumed annually in the 62 urban centers within central Amazonia, the equivalent of 6.49 kg per person per year. In monetary terms, this amounts to US$21.72 per person per year or US$35.1 million overall, the latter figure is comparable to fish and timber production in the region. Given this magnitude of wild meat trade in central Amazonia, it is fundamental to integrate this activity into the formal economy and actively develop policies that allow the trade of more resilient taxa and restrict trade in species sensitive to hunting.

Nutritive Value and Enteric Methane Production of Brachiaria spp. Under Elevated [CO2] - A. L. Abdalla; A. L. Abdalla Filho; A. S. Natel; H. Louvandini; M. C. Piccolo; K. L. Nechet; A. Torre Neto; R. Ghini (International Journal of Plant Production, 2020)

Bloodstream Infection of a Cancer Patient by Cystobasidium minutum: A Case Report and Literature Review - Cicero P. Inácio; Madi V. Diniz; Paulo Sergio R. Araújo; Marilane S. Barros; Melyna C. L. Andrade; Reginaldo G. Lima-Neto; Danielle Patrícia C. Macêdo; Rejane P. Neves (Mycopathologia, 2020)

Guanosine and GMP increase the number of granular cerebellar neurons in culture: dependence on adenosine A2A and ionotropic glutamate receptors - Helena Decker; Tetsade C. B. Piermartiri; Cláudia B. Nedel; Luciana F. Romão; Sheila S. Francisco; Tharine Dal-Cim; Carina R. Boeck; Vivaldo Moura-Neto; Carla I. Tasca (Purinergic Signalling, 2019)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Which Species of Coconut Moth Occurs in Brazil: Atheloca subrufella vs. Atheloca bondari (Lepidoptera: Pyralidae)? - A A Paz-Neto; M. T. S. Freitas; M. G. C. Gondim; J. W. S. Melo; R. B. Querino; V. Q. Balbino (Neotropical Entomology, 2019)

A review of current uses and potential biotechnological applications of seaweeds from the Macaronesian region (Central-East Atlantic Ocean) - R. Haroun; M. C. Gil-Rodríguez; A. I. Neto; M. Machín-Sánchez; M. A. Viera-Rodríguez (Journal of Applied Phycology, 2019)

The Absence of Pineal Melatonin Abolishes the Daily Rhythm of Tph1 (Tryptophan Hydroxylase 1), Asmt (Acetylserotonin O-Methyltransferase), and Aanat (Aralkylamine N-Acetyltransferase) mRNA Expressions in Rat Testes - L. A. Coelho; J. Andrade-Silva; L. C. Motta-Teixeira; F. G. Amaral; R. J. Reiter; J. Cipolla-Neto (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The role of therapy with aminoglycoside in the outcomes of kidney transplant recipients infected with polymyxin- and carbapenem-resistant Enterobacteriaceae - Maristela P. Freire; Doroti de Oliveira Garcia; Ana Paula Cury; Gabriela R. Francisco; Nathamy F. dos Santos; Fernanda Spadão; Maria Fernanda Campagnari Bueno; Carlos Henrique Camargo; Flavio J. de Paula; Flavia Rossi; Willian C. Nahas; Elias David-Neto; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Toxicity of Diflubenzuron and Temephos on Freshwater Fishes: Ecotoxicological Assays with Oreochromis niloticus and Hyphessobrycon eques - Flavia R. Abe; Angela A. Machado; Ana C. Coleone; Claudinei da Cruz; Joaquim G. Machado-Neto (Water, Air, & Soil Pollution, 2019)

Studies of NMR, molecular docking, and molecular dynamics simulation of new promising inhibitors of cruzaine from the parasite Trypanosoma cruzi - Renato A. Costa; Jorddy N. Cruz; Fabiana C. A. Nascimento; Sebastião G. Silva; Silvana O. Silva; Marlice C. Martelli; Samira M. L. Carvalho; Cleydson B. R. Santos; Antonio M. J. C. Neto; Davi S. B. Brasil (Medicinal Chemistry Research, 2019)

Arabica coffee progenies with multiple resistant to root-knot nematodes - Ramiro M. Rezende; Vinicius T. Andrade; Sonia M. L. Salgado; Juliana C. de Rezende; Tiago G. C. Neto; Gladyston R. Carvalho (Euphytica, 2019)

Intra‐clade metabolomic profiling of MAR4 Streptomyces from the Macaronesia Atlantic region reveals a source of anti‐biofilm metabolites - Anelize Bauermeister; Florbela Pereira; Inês R. Grilo; Camila C. Godinho; Marisa Paulino; Vanessa Almeida; Leonardo Gobbo‐Neto; Alejandra Prieto‐Davó; Rita G. Sobral; Norberto P. Lopes; Susana P. Gaudêncio (Environmental Microbiology, 2019)
Summary The search for new and effective strategies to reduce bacterial biofilm formation is of utmost importance as bacterial resistance to antibiotics continues to emerge. The use of anti‐biofilm agents that can disrupt recalcitrant bacterial communities can be an advantageous alternative to antimicrobials, as their use does not lead to the development of resistance mechanisms. Six MAR4 Streptomyces strains isolated from the Madeira Archipelago, at the unexplored Macaronesia Atlantic ecoregion, were used to study the chemical diversity of produced hybrid isoprenoids. These marine actinomycetes were investigated by analysing their crude extracts using LC–MS/MS and their metabolomic profiles were compared using multivariate statistical analysis (principal component analysis), showing a separation trend closely related to their phylogeny. Molecular networking unveiled the presence of a class of metabolites not previously described from MAR4 strains and new chemical derivatives belonging to the napyradiomycin and marinone classes. Furthermore, these MAR4 strains produce metabolites that inhibit biofilm formation of Staphylococcus aureus and Marinobacter hydrocarbonoclasticus . The anti‐biofilm activity of napyradiomycin SF2415B3 ( 1 ) against S. aureus was confirmed.

Intra- and interspecific genetic divergence in Macroptilium (Benth.) Urb.: a forage option for Brazilian semiarid - R. O. Borges; R. P. Antonio; J. L. da Silva Neto; I. C. de S. A. Lira (Genetic Resources and Crop Evolution, 2019)

Negative inotropism of terpenes on guinea pig left atrium: structure-activity relationships - Carla M. L. Vasconcelos; Ingrid S. N. Oliveira; José N. A. Santos; Américo A. Souza; José E. R. Menezes-Filho; Júlio A. Silva Neto; Tamires C. Lima; Damião P. de Sousa (Natural Product Research, 2018)

Ticks (Acari: Ixodidae) of the state of Amazonas, Brazil - Sergio L. Gianizella; Thiago F. Martins; Valeria C. Onofrio; Nair O. Aguiar; Waleska Gravena; Carlos A. R. do Nascimento; Laérzio C. Neto; Diogo L. Faria; Natália A. S. Lima; Monica R. Solorio; Louise Maranhão; Ivan J. Lima; et al. (Experimental and Applied Acarology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Serological and molecular markers of hepatitis E virus infection in HIV-infected patients in Brazil - A. C. Ferreira; Michele Soares Gomes-Gouvêa; G. Lisboa-Neto; M. C. J. Mendes-Correa; C. M. Picone; N. A. Salles; A. Mendrone-Junior; F. J. Carrilho; J. R. R. Pinho (Archives of Virology, 2018)

Land Use Effect on the CN Model Parameters in a Tropical Dry Environment - E. M Andrade; J. R Araújo Neto; M. J. S Guerreiro; J. C. N Santos; H. A. Q Palácio (Water Resources Management, 2017)

Environmental control of adventitious rooting in Eucalyptus and Populus cuttings - M. R. De Almeida; M. Aumond; C. T. Da Costa; J. Schwambach; C. M. Ruedell; L. R. Correa; A. G. Fett-Neto (Trees, 2017)

Quercetin inhibits gout arthritis in mice: induction of an opioid-dependent regulation of inflammasome - Kenji W. Ruiz-Miyazawa; Larissa Staurengo-Ferrari; Sandra S. Mizokami; Talita P. Domiciano; Fabiana T. M. C. Vicentini; Doumit Camilios-Neto; Wander R. Pavanelli; Phileno Pinge-Filho; Flávio A. Amaral; Mauro M. Teixeira; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2017)

Cylindrospermopsin effects on cell viability and redox milieu of Neotropical fish Hoplias malabaricus hepatocytes - R. C. Silva; S. Liebel; H. H. P. de Oliveira; W. A. Ramsdorf; J. R. E. Garcia; S. M. F. O. Azevedo; V. F. Magalhães; C. A. Oliveira Ribeiro; F. Filipak Neto (Fish Physiology and Biochemistry, 2017)

Regulation of the photosynthetic electron transport and specific photoprotective mechanisms in Ricinus communis under drought and recovery - Milton C. Lima Neto; Joaquim Albenísio G. Silveira; João V. A. Cerqueira; Juliana R. Cunha (Acta Physiologiae Plantarum, 2017)

Design of Magnetic Polymeric Particles as a Stimulus-Responsive System for Gastric Antimicrobial Therapy - Erica L. Silva-Freitas; Thales R. F. Pontes; Rafael P. Araújo-Neto; Ítalo H. M. Damasceno; Kátia L. Silva; Juliana F. Carvalho; Aldo C. Medeiros; Rodolfo B. Silva; Amanda K. A. Silva; Marco A. Morales; Eryvaldo S. T. Egito; Ana L. Dantas; et al. (AAPS PharmSciTech, 2017)

Labeling of adipose-derived stem cells with quantum dots provides stable and long-term fluorescent signal for ex vivo cell tracking - Clautina R. M. Costa; Matheus L. T. Feitosa; Dayseanny O. Bezerra; Yulla K. P. Carvalho; Rodrigo F. G. Olivindo; Pablo B. Fernando; Gustavo C. Silva; Mirna L. G. Silva; Carlos E. Ambrósio; Airton M. Conde Júnior; Napoleão M. Argolo Neto; Laís M. Costa Silva; et al. (In Vitro Cellular & Developmental Biology - Animal, 2017)

Deconstructing the relationships between phylogenetic diversity and ecology: a case study on ecosystem functioning - T. Jonathan Davies; Mark C. Urban; Bronwyn Rayfield; Marc W. Cadotte; Pedro R. Peres‐Neto (Ecology, 2016)
Recent studies have supported a link between phylogenetic diversity and various ecological properties including ecosystem function. However, such studies typically assume that phylogenetic branches of equivalent length are more or less interchangeable. Here we suggest that there is a need to consider not only branch lengths but also their placement on the phylogeny. We demonstrate how two common indices of network centrality can be used to describe the evolutionary distinctiveness of network elements (nodes and branches) on a phylogeny. If phylogenetic diversity enhances ecosystem function via complementarity and the representation of functional diversity, we would predict a correlation between evolutionary distinctiveness of network elements and their contribution to ecosystem process. In contrast, if one or a few evolutionary innovations play key roles in ecosystem function, the relationship between evolutionary distinctiveness and functional contribution may be weak or absent. We illustrate how network elements associated with high functional contribution can be identified from regressions between phylogenetic diversity and productivity using a well‐known empirical data set on plant productivity from the Cedar Creek Long‐Term Ecological Research. We find no association between evolutionary distinctiveness and ecosystem functioning, but we are able to identify phylogenetic elements associated with species of known high functional contribution within the Fabaceae. Our perspective provides a useful guide in the search for ecological traits linking diversity and ecosystem function, and suggests a more nuanced consideration of phylogenetic diversity is required in the conservation and biodiversity–ecosystem‐function literature.

Phylogenenetic approach of the section Bulbocodii D.C. of Narcissus based on cpDNA. A case of taxonomic inflation? - J. P. Fonseca; A. Levy; R. Henriques; J. C. Costa; C. Neto; J. Robalo (Plant Biosystems, 2016)

CMA band variability and physical mapping of 5S and 45S rDNA sites in Brazilian Cactaceae: Pereskioideae and Opuntioideae - Juliana P. Castro; Enoque Medeiros-Neto; Gustavo Souza; Lânia I. F. Alves; Fabiane R. C. Batista; Leonardo P. Felix (Brazilian Journal of Botany, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Antimicrobial Activity of ILTI, a Kunitz‐Type Trypsin Inhibitor from Inga laurina (SW.) Willd - Maria Lígia R. Macedo; Suzanna F. F. Ribeiro; Gabriel B. Taveira; Valdirene M. Gomes; Karina M. C. A. de Barros; Simone Maria-Neto (Current Microbiology, 2016)

RNA-seq transcriptional profiling of Herbaspirillum seropedicae colonizing wheat (Triticum aestivum) roots - V. C. S. Pankievicz; D. Camilios-Neto; P. Bonato; E. Balsanelli; M. Z. Tadra-Sfeir; H. Faoro; L. S. Chubatsu; L. Donatti; G. Wajnberg; F. Passetti; R. A. Monteiro; F. O. Pedrosa; et al. (Plant Molecular Biology, 2016)

Effects of realistic concentrations of TiO2 and ZnO nanoparticles in Prochilodus lineatus juvenile fish - R. R. Miranda; A. L. R. Damaso da Silveira; I. P. de Jesus; S. R. Grötzner; C. L. Voigt; S. X. Campos; J. R. E. Garcia; M. A. F. Randi; C. A. Oliveira Ribeiro; F. Filipak Neto (Environmental Science and Pollution Research, 2016)

Environmental tobacco smoke in the early postnatal period induces impairment in brain myelination - Larissa H. Torres; Raquel Annoni; Natalia T. Balestrin; Priscila L. Coleto; Stephanie O. Duro; Raphael C. T. Garcia; Maurílio Pacheco-Neto; Thais Mauad; Rosana Camarini; Luiz R. G. Britto; Tania Marcourakis (Archives of Toxicology, 2015)

Contribution of agroforests to landscape carbon storage - Götz Schroth; Lucio C. Bede; Artur O. Paiva; Camila R. Cassano; André M. Amorim; Deborah Faria; Eduardo Mariano-Neto; Adriana M. Z. Martini; Regina H. R. Sambuichi; Renato N. Lôbo (Mitigation and Adaptation Strategies for Global Change, 2015)

Neonatal Candidemia Caused by Candida haemulonii: Case Report and Review of Literature - Carolina M. Silva; Ana M. R. Carvalho-Parahym; Danielle P. C. Macêdo; Reginaldo G. Lima-Neto; Elaine C. Francisco; Analy S. A. Melo; Maria da Conceição M. Silva; Moacir B. Jucá; Luciana R. B. Mello; Rosemary M. J. Amorim; Rejane P. Neves (Mycopathologia, 2015)

Ability of immunodiagnostic tests to differentiate between dogs naturally infected with Leishmania infantum and Leishmune®-vaccinated dogs - R. A. N. Ribeiro; R. G. Teixeira-Neto; V. S. Belo; E. C. Ferreira; H. D. F. H. Schallig; E. S. Silva (Veterinary Research Communications, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

Trophic ecology and food consumption of fishes in a hypersaline tropical lagoon - P. H. Almeida‐Silva; R. A. Tubino; L. C. Zambrano; D. A. Hunder; S. R. Garritano; C. Monteiro‐Neto (Journal of Fish Biology, 2015)
This study evaluated the trophic ecology (diet composition, trophic strategy, similarities and overlap between species, feeding period and food consumption) of six benthivorous fish species in Araruama Lagoon, the largest hypersaline tropical lagoon on the east coast of South America, with an area of 210 km 2 and an average salinity of 52. The burrfish Chilomycterus spinosus fed on Anomalocardia flexuosa shell deposits, ingesting associated fauna. The caitipa mojarra Diapterus rhombeus differed from all other species, having not only the highest proportions of algae and Nematoda, but also feeding on polychaete tentacles. The two mojarras Eucinostomus spp. showed similar trophic strategies, feeding mostly on Polychaeta. The corocoro grunt Orthopristis ruber also fed mainly on Polychaeta, but differed from Eucinostomus spp. in secondary items. The whitemouth croacker Micropogonias furnieri fed mainly on small Crustacea at night, showing a high number of secondary prey items with low frequencies and high prey‐specific abundance. The daily food consumption (g food g −1 fish mass) for Eucinostomus argenteus was 0·012 and was 0·031 and 0·027 for M. furnieri in two different sampling events. The diet similarities between Araruama Lagoon and other brackish and marine environments indicate that hypersalinity is not a predominant factor shaping the trophic ecology of fishes in this lagoon. The stability of hypersaline conditions, without a pronounced gradient, may explain the presence of several euryhaline fishes and invertebrates well adapted to this condition, resulting in a complex food web.

Embryo development, fetal growth and postnatal phenotype of eGFP lambs generated by lentiviral transgenesis - M. Crispo; M. Vilariño; P. C. dos Santos-Neto; R. Núñez-Olivera; F. Cuadro; N. Barrera; A. P. Mulet; T. H. Nguyen; I. Anegón; A. Menchaca (Transgenic Research, 2015)

Parasitoid Wasps in Flower Heads of Asteraceae in the Brazilian Cerrado: Taxonomical Composition and Determinants of Diversity - A R Nascimento; M Almeida-Neto; A M Almeida; C R Fonseca; T M Lewinsohn; A M Penteado-Dias (Neotropical Entomology, 2014)

Photosynthesis, antioxidant activities and transcriptional responses in two sugarcane (Saccharum officinarum L.) cultivars under salt stress - Camila D. Medeiros; José R. C. Ferreira Neto; Marciel T. Oliveira; Rebeca Rivas; Valesca Pandolfi; Éderson A. Kido; José. I. Baldani; Mauro G. Santos (Acta Physiologiae Plantarum, 2014)

Eucalypt growth in monoculture and silvopastoral systems with varied tree initial densities and spatial arrangements - Ranieri R. Paula; Geraldo G. Reis; Maria G. F. Reis; Sílvio N. Oliveira Neto; Helio G. Leite; Raul C. N. Melido; Hortênsia N. S. Lopes; Felippe C. Souza (Agroforestry Systems, 2013)

Purinergic and glutamatergic interactions in the hypothalamic paraventricular nucleus modulate sympathetic outflow - H. C. Ferreira-Neto; S. T. Yao; V. R. Antunes (Purinergic Signalling, 2013)

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Antifolates inhibit Cryptococcus biofilms and enhance susceptibility of planktonic cells to amphotericin B - R. Aguiar Cordeiro; C. I. Mourão; M. F. G. Rocha; F. J. Farias Marques; C. E. C. Teixeira; D. F. Oliveira Miranda; L. V. P. Neto; R. S. N. Brilhante; T. Jesus Pinheiro Gomes Bandeira; J. J. C. Sidrim (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Ubiquitous urease affects soybean susceptibility to fungi - Beatriz Wiebke-Strohm; Giancarlo Pasquali; Márcia Margis-Pinheiro; Marta Bencke; Lauro Bücker-Neto; Arlete B. Becker-Ritt; Anne H. S. Martinelli; Ciliana Rechenmacher; Joseph C. Polacco; Renata Stolf; Francismar C. Marcelino; Ricardo V. Abdelnoor; et al. (Plant Molecular Biology, 2012)

Water Deficit and Salt Stress Diagnosis Through LED Induced Chlorophyll Fluorescence Analysis in Jatropha curcas L. - E. A. Silva; A. S. Gouveia-Neto; R. A. Oliveira; D. S. Moura; P. C. Cunha; E. B. Costa; T. J. R. Câmara; L. G. Willadino (Journal of Fluorescence, 2012)

Levels of oxidative stress markers: correlation with hepatic function and worm burden patients with schistosomiasis - G. Cunha; V. Silva; K. Bessa; M. Bitencourt; U. Macêdo; F. Freire-Neto; R. Martins; C. Assis; T. Lemos; M. Almeida; A. Freire (Acta Parasitologica, 2012)
Schistosomiasis is caused by Schistosoma mansoni and is a public health problem in Brazil. The typical granulomatous lesion is associated with the increase in the oxidative damage by generation of free radicals. The aim of this work was to correlate some oxidative stress markers with the worm burden on carriers of schistosomiasis (n = 30) in the acute phase in comparison to healthy subjects (n = 30). The pro-oxidant parameter used was the colorimetric quantification of reactive substances to thiobarbituric acid, while the antioxidant markers used were blood content of reduced glutathione and determination of the activity of catalase. The worm burden was assessed by Kato-Katz method. The results pointed out that initially there was no difference in the catalase activity. However, there was a positive correlation between the increase in parasitic load and intensity of lipid peroxidation, and decrease in the content of reduced glutathione. Additionally, only the aspartate aminotransferase levels presented to be high, while there was a decrease in bilirubin level. Therefore, a possible association between the establishment of the oxidative stress in tissue and the parasitic load of Schistosoma mansoni is suggested.

The Itajaí foreland basin: a tectono-sedimentary record of the Ediacaran period, Southern Brazil - M. A. S. Basei; C. O. Drukas; A. P. Nutman; K. Wemmer; L. Dunyi; P. R. Santos; C. R. Passarelli; M. C. Campos Neto; O. Siga; L. Osako (International Journal of Earth Sciences, 2011)

Prevalence of Leptospira interrogans antibodies in free-ranging Tayassu pecari of the Southern Pantanal, Brazil, an ecosystem where wildlife and cattle interact - Tatiana P. Tavares de Freitas; Alexine Keuroghlian; Donald P. Eaton; Emanuel Barbosa de Freitas; Aline Figueiredo; Luciano Nakazato; Jacqueline M. de Oliveira; Flávia Miranda; Rita Cassia S. Paes; Leticia A. R. Carneiro Monteiro; José Vergílio B. Lima; Aparecida A. da C. Neto; et al. (Tropical Animal Health and Production, 2010)

Involvement of ethylene in the rooting of seedling shoot cultures of Bixa orellana L. - Vespasiano Borges Paiva Neto; Luciano B. Reis; Fernando L. Finger; Raimundo S. Barros; Carlos R. Carvalho; Wagner C. Otoni (In Vitro Cellular & Developmental Biology - Plant, 2009)

Distribution of pteridophyte communities along environmental gradients in Central Amazonia, Brazil - Gabriela Zuquim; Flávia R. C. Costa; Jefferson Prado; Ricardo Braga-Neto (Biodiversity and Conservation, 2009)

Spherical harmonic analysis of earth’s conductive heat flow - V. M. Hamza; R. R. Cardoso; C. F. Ponte Neto (International Journal of Earth Sciences, 2008)

Reply to comments by Henry N. Pollack and David S. Chapman on “Spherical harmonic analysis of Earth’s conductive heat flow” - V. M. Hamza; R. R. Cardoso; C. F. Ponte Neto (International Journal of Earth Sciences, 2008)

The use of nursery areas by juvenile fish in a temperate estuary, Portugal - Filipe Martinho; R. Leitão; J. M. Neto; H. N. Cabral; J. C. Marques; M. A. Pardal (Hydrobiologia, 2007)

Milk-clotting protease production by Nocardiopsis sp. in an inexpensive medium - M. T. H. Cavalcanti; C. R. Martinez; V. C. Furtado; B. B. Neto; M. F. Teixeira; J. L. Lima Filho; A. L. F. Porto (World Journal of Microbiology and Biotechnology, 2005)

Effects of Copper Oxychloride in Rana catesbeiana Tadpoles: Toxicological and Bioaccumulative Aspects - C. M. Ferreira; J. V. Lombardi; J. G. Machado-Neto; H. M. Bueno-Guimares; S. R. C. Soares; P. H. N. Saldiva (Bulletin of Environmental Contamination and Toxicology, 2004)

Axillary bud development of passionfruit as affected by ethylene precursor and inhibitors - L. B. Reis; V. B. Paiva Neto; E. A. Toledo Picoli; M. G. C. Costa; M. M. Rêgo; C. R. Carvalho; F. L. Finger; W. C. Otoni (In Vitro Cellular & Developmental Biology - Plant, 2003)

Acute Toxicity of the Fungicide Copper Oxychloride to Tadpoles of the Bullfrog Rana catesbeiana - J. V. Lombardi; T. R. Perpétuo; C. M. Ferreira; J. G. Machado-Neto; H. L. A. Marques (Bulletin of Environmental Contamination and Toxicology, 2002)

Prevalence of GB Virus C (Hepatitis G Virus) and Risk Factors for Infection in São Paulo, Brazil - Ribeiro-dos-Santos G.; Nishiya A.; Nascimento C.; Bassit L.; Chamone D.; Focaccia R.; Eluf-Neto J.; Sabino E. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Safety Measures in the Application of Organophosphate Insecticides on Staked Tomato Crops Using Dragged Hoses - M. E. C. Queiroz; J. G. Machado-Neto; L. R. L. Pereira; F. Calixto; F. D. Amarolli; N. S. Arakawa; D. Carvalho (Bulletin of Environmental Contamination and Toxicology, 2002)

Phagocytosis and giant cell formation at 0° C by macrophage (MØ) of Notothenia coriiceps - J. R. M. C. Silva; N. A. Staines; F. J. Hernandez‐Blazquez; L. R. Porto‐Neto; J. C. S. Borges (Journal of Fish Biology, 2002)
Macrophages adhered to round glass coverslips that had been implanted into the abdominal cavity of Notothenia coriiceps , collected from Admiralty Bay, King George Island, and removed and incubated in vitro for 4 h at 0° C at various intervals. The macrophages phagocytosed yeast Saccharomyces cerevisiae cells suspended in saline. Bi‐nuclear macrophages were first observed after 6 h. The formation of giant cells and their phagocytic activity was observed only in fish which had been injected with 1 ml of Bacillus of Calmette and Guerin (BCG)‐suspension 24 h before coverslip implantation and the coverslips removed 15 days after the implantation. Phagocytosis and the formation of giant cells in an Antarctic fish at 0° C is described for the first time.

Optimisation of medium composition for clavulanic acid production by Streptomyces clavuligerus - Ester R. Gouveia; Alvaro Baptista-Neto; Alberto C. Badino Jr; Carlos O. Hokka (Biotechnology Letters, 2001)

Urease activity and its relation to soil organic matter, microbial biomass nitrogen and urea-nitrogen assimilation by maize in a Brazilian Oxisol under no-tillage and tillage systems - R. Roscoe; C. A. Vasconcellos; A. E. Furtini-Neto; G. A. A. Guedes; L. A. Fernandes (Biology and Fertility of Soils, 2000)

Titi monkeys (Callicebus spp., Atelidae: Platyrrhini) in the Brazilian state of Rondônia - Stephen F. Ferrari; Simone Iwanaga; Mariluce R. Messias; Eleildon M. Ramos; Paulo C. S. Ramos; Ernesto H. da Cruz Neto; Paulo E. G. Coutinho (Primates, 2000)

Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in Southwestern Amazonia - Stephen F. Ferrari; Simone Iwanaga; Paulo E. G. Coutinho; Mariluce R. Messias; Ernesto H. Cruz Neto; Eleildon M. Ramos; Paulo C. S. Ramos (International Journal of Primatology, 1999)

Improvement of clavulanic acid production by Streptomyces clavuligerus in medium containing soybean derivatives - Ester R. Gouveia; Alvaro Baptista-Neto; Amadeus G. Azevedo; Alberto C. Badino; Carlos O. Hokka (World Journal of Microbiology and Biotechnology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Behavioral ecology ofMyiopharus doryphorae (riley) andM. aberrans (townsend), tachinid parasitoids of the colorado potato beetle - E. R. López; L. C. Roth; D. N. Ferro; D. Hosmer; A. Mafra-Neto (Journal of Insect Behavior, 1997)

Morphology, biology and pesticide tolerance ofChelotogenes ornatus [Acari: Cheyletidae] - G. J. Moraes; R. S. Neto; H. C. S. Pinto (BioControl, 1989)